Spatiotemporal gait parameters and plantar pressure distribution during barefoot walking in people with gout and asymptomatic hyperuricemia: comparison with healthy individuals with normal serum urate concentrations. Issue 1 (December 2016) - Stewart, Sarah; Dalbeth, Nicola; Vandal, Alain; Rome, Keith
Abstract Background To identify spatiotemporal gait parameters and plantar pressure distribution during barefoot walking in people with gout and people with asymptomatic hyperuricemia by comparing them to healthy individuals with normal serum urate concentrations. Methods Eighty-seven participants were included: 24 with gout, 29 with asymptomatic hyperuricemia and 34 age- and sex-matched normouricemic control participants. Spatiotemporal parameters of gait were assessed during level barefoot walking using a GAITRite® walkway. Peak plantar pressure and pressure time integrals were recorded using a TekScan MatScan®. Results were adjusted for age and body mass index. Results Compared to normouricemic control participants, participants with gout demonstrated increased step time (P = 0.022) and stance time (P = 0.022), and reduced velocity (P = 0.050). Participants with gout also walked with decreased peak pressure at the heel (P = 0.012) and hallux (P = 0.036) and increased peak pressure (P < 0.001) and pressure time integrals (P = 0.005) at the midfoot. Compared to normouricemic control participants, participants with asymptomatic hyperuricemia demonstrated increased support base (P = 0.002), double support time (P < 0.001) and cadence (P = 0.028) and reduced swing time (P = 0.019) and single support time (P = 0.020) as well as increased pressure at the midfoot (P = 0.013), first metatarsal (P = 0.015) and second metatarsal (P = 0.007). Conclusion During barefoot walking, people with gout walk slower with plantar pressure patterns suggestive of apropulsive and antalgic gait strategies. Individuals with asymptomatic hyperuricemia also demonstrate altered barefoot gait patterns when compared to normouricemic control participants. Clinicians may consider dynamic gait outcomes when assessing and managing foot and lower limb related pain and disability in individuals with gout and asymptomatic hyperuricemia.